The Effect of E-Service Quality, E-Trust and E-Satisfaction on Repurchase Intention through Prior Online Experience as a Moderation Variable : (Empirical Study on Tokopedia E-Commerce Service Users in Padang City) - M Nabil Akmal; Thamrin Thamrin (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of e-service quality, e-trust, and e-satisfaction on the repurchase intention of Tokopedia marketplace customers in Padang City, and to examine the role of prior online experience as a moderating variable in this relationship.The study uses a quantitative approach with hypothesis testing to test the causal relationship between the independent and dependent variables. Based on the results of data analysis, it was found that e-service quality and e-satisfaction have a positive and significant effect on repurchase intention, while e-trust does not have a significant effect on repurchase intention. Regarding the role of prior online experience as a moderating variable, the results of the study show that previous online shopping experience is able to moderate (strengthen) the relationship between e-service quality and repurchase intention as well as the relationship between e-satisfaction and repurchase intention. However, prior online experience failed to moderate the relationship between e-trust and repurchase intention. Based on the results of the analysis, it shows that the quality of electronic services and customer satisfaction supported by previous positive experiences are key factors that drive repurchase intention on the Tokopedia marketplace, while consumer trust does not relatively affect repurchase intention in the context of this study.